Pemanfaatan Media Sosial dalam Pemasaran Produk UMKM Bu Wati di Desa Sumberejo Kabupaten Pasuruan - Muhammad Rifal Ramadhan; Fatchur Rozci (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2023)
UMKM actors are one of the jobs of the majority of the people in Sumberejo Village. The lack of information and technology for UMKM regarding social media technology in Industry 4.0 which is very helpful for UMKM to make sales online. Community service activities are carried out with outreach and assistance to provide knowledge and application of social media to market UMKM products. This activity went through four stages, namely the planning, preparation, socialization, and mentoring stages. Socialization and mentoring activities are carried out by teaching social media which consists of registration to completion. The existence of socialization regarding social media can help UMKM actors to facilitate sales in Industry 4.0